Crowdfunding as a Tool to Achieve Economic Inclusion for Youth: Evidence from Morocco - EL RHIOUANE , Bouchra; BOUZAHZAH , Mohamed; ZAOUJAL , Nouzha; ANGOUR , Nora (Revue Internationale des Sciences de Gestion, 2024)
Morocco, like many developing countries, faces significant challenges in achieving economic inclusion for its youth. Despite progress in various sectors, a substantial portion of the young population remains excluded from economic opportunities. In this context, crowdfunding emerges as a potentially effective tool to enhance the financial and economic inclusion of young Moroccans. However, understanding the extent to which crowdfunding can address the specific needs of this demographic is crucial. This paper examines the current landscape of crowdfunding in Morocco and its potential to facilitate economic inclusion for the youth. To achieve this, a quantitative study involving 120 young Moroccans was conducted. The findings reveal that the primary obstacle for aspiring young entrepreneurs in Morocco is financial constraints, compounded by a lack of entrepreneurial and financial skills. Crowdfunding could potentially address these barriers and foster economic inclusion for young Moroccans. Nonetheless, substantial efforts are needed to increase awareness and understanding of this financing method among the youth. The study indicates that, while crowdfunding holds promise, its success hinges on concerted efforts to educate and inform young people about its benefits and mechanisms. By promoting financial literacy and entrepreneurial skills alongside crowdfunding, Morocco can create a more inclusive economic environment for its youth.